(untitled) (Faridpur Medical College Journal, 2013)
Strongyloides stercoralis is a common intestinal parasite in tropics and subtropics. In Bangladesh, prevalence is likely to be high due to poor sanitation. Clinical presentations are frequently nonspecific. However, in immunosuppressed individuals, infection becomes overwhelming and may disseminate and results in high rates of mortality. Unless a high index of suspicion, this readily treatable disease may be missed. Here we report a case of hyperinfection with Strongyloides stercoralis in a patient who was on corticosteroid treatment. A 45 years old male was admitted in Gastroenterology department of Bangabandhu Sheikh Mujib Medical University (BSMMU) with the complaints of abdominal pain, vomiting and diarrhea for 2 weeks. He was on prednisolone 60 mg with omeprazole 40 mg daily for 4 weeks for his eyelid drooping prior to the development of abdominal symptoms. Physical examination revealed a severely malnourished, moderately anemic patient with muscle wasting, angular stomatitis, desquamated skins of feet and hands. Abdominal examination revealed generalized tenderness with moderate ascites. Investigations revealed Hb-7.4 gm/dl with normal WBC count (eosinophil-11% before steroid therapy), S.albumin-19gm/l with prolonged prothrombin time and hypokalemia. USG of abdomen revealed moderate ascites. Endoscopy of upper GIT showed congestion and multiple erosions in the stomach and also in the duodenum. Biopsy from the duodenum revealed adult Strongyloides stercoralis on the surface, larva and ova in the duodenal crypts. The patient was treated with 10 days of oral ivermectin along with blood transfusion, correction of nutritional status and electrolyte imbalance. Patient was discharged home after a total of 20 days of hospitalization DOI: http://dx.doi.org/10.3329/fmcj.v7i2.13526 Faridpur Med. Coll. J. 2012;7(2):98-101